Spasticity-Plus syndrome in multiple sclerosis patients in a tertiary hospital in Spain - Goicochea Briceño, Haydee; Higueras, Yolanda; Ruiz Pérez, Irene; García Domínguez, José Manuel; Cuello, Juan Pablo; Meldaña Rivera, Ariana; Martínez Ginés, María Luisa (Frontiers in Neurology, 2024)
Introduction Spasticity is a common symptom in multiple sclerosis (MS) and it is often associated with other symptoms such as spasms/cramps and pain. The concept of Spasticity-Plus syndrome takes into account that spasticity is accompanied by one or more symptoms (spasms/cramps, pain, bladder dysfunction, sleep disorders, fatigue and/or tremor). As these symptoms share a common cannabinoid control, therapy acting on cannabinoid receptors may be useful. The main study objectives were to determine the number of MS patients who met Spasticity-Plus syndrome criteria and to identify the most common symptoms. Methods Clinical records of MS patients treated with nabiximols in a tertiary hospital from 2002 to 2022 were reviewed retrospectively. Results Of the 73 patients included in the study, 53.4% were women, and most had secondary progressive MS (64.4%). All patients met the criteria for Spasticity-Plus syndrome: 100% had spasticity and at least another symptom. Pain was the second most common symptom (91.8%), followed by spasms/cramps (79.4%), and fatigue (76.7%). Sleep disturbances (p < 0.0001) and tremor (p < 0.027) were more frequent in patients with relapsing–remitting MS than in patients with progressive MS. No statistically significant differences were found for spasticity, pain, spasms/cramps, and fatigue between MS phenotypes. Regarding symptoms clusters, 94.4% of the patients had three or more symptoms. Spasticity was more frequently associated with pain (91.8%) and spasms/cramps (79.4%). Conclusion Spasticity-Plus syndrome was present in all the study population of patients with different MS phenotypes, and treated with nabiximols.